Determinants Of Stock Price Factors In The Jakarta Islamic Index - Kuswara, Adriana; Damayanti, Damayanti (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2024)
Information plays a vital role in stock trading in the capital market, especially for investors who plan to engage in investment activities in the capital market. The purpose of this study is to analyze the effect of return on equity (ROE), earning per share (EPS), and price to book value (PBV) on stock prices. The study population was 30 companies listed on the Jakarta Islamic Index on the IDX. A purposive sampling technique obtained 7 samples with 34 observation data. The data analysis technique used multiple linear regressions. The study results showed that ROE and EPS did not affect stock prices, but PBV positively affected stock prices. This study can increase knowledge and complement existing theories, especially regarding PBV and stock prices, and can be a reference for further research. This study can be a reference for investors and potential investors who are investing their capital in the company so as not to experience losses and for company managers to make decisions to maintain stock price stability.